The Fading of an Archimedean Point - Marita Tatari (Performance Philosophy, 2022)
Instead of a new “turn” of forms, the current landscape of performing arts is dominated by an immediate demand for political relevance, as well as by a correlative feeling of powerlessness. This can, however, no longer be grasped in terms of an opposition between autonomous and politically engaged art, because the framework of this opposition can no longer apply. Drawing on a distinction between renegotiation of power and desire, and transferring it into the field of performing arts, allows me to address epistemologically the shift we are currently facing. The emergence of new forms, as well as the way they are received, testify to the fading of an Archimedean point, the fading of a point from which to cast an eye on the artistic process of the emergence of forms. Hannah Arendt’s The Human Condition becomes then strangely relevant. She advocates the unconditional that comes to the fore with the human condition, while criticizing harshly the utilitarian consequences of the discovery of an Archimedean point in western cultural history. I argue that reconsidering “stage” and “audience” as space of appearance, we can take a stand for that which punctuates the emergence of forms, without considering it from an Archimedean point.